Brain bioelectricity activity of the sportsmen underwent the neurobiofeedback course - S. P. Styopochkina; L. P. Cherapkina; V. G. Tristan (Бюллетень сибирской медицины)
The EEG analysis of the 26 highly qualified sportsmen shows, that the brain bioelectricity activity is changed by the neurobiofeedback. It relates with the alpha-rhythm and with the greatest neurodynamic changings in the right hemisphere. The after training EEG changings have the sex differences. Everything fields of the right hemisphere and the temporal-occipital field of the left hemisphere of the sportsmen-male and the forward-temporal of left hemisphere and the central-occipital field of both hemispheres of the sportswomen work during the neurodynamic changing.